The struggling tobacco policies: political economy of tobacco in Turkey, 1938 - 1984 - Gürsoy, Özgür Burçak. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2014., 2014)
This study examines the political economy of the Turkish tobacco market between 1938 and 1984. It discusses the struggling tobacco policies of the market actors, including TEKEL, the merchants, experts, and producers. The discussion is based primarily on documents from the Prime Ministry State Archives and personal archives of two high-ranking Monopoly managers, four different sector journals, newspaper reports, congress proceedings and interviews with sector representatives. The conclusions reached are both informative and challenging for the modem Turkish historiography. This dissertation first concludes that the policy formulation and implementation were not top-down processes, but shaped by the political and social power balance among the market actors during the era under discussion. Second, the organizational representation of the merchants, experts and producers was crucial in policy-making as early as the 1940s. Besides their organizational activities, the market actors provided short-term benefits via petitioning, negotiating, sale boycotting and holding demonstrations through the period. Third, tobacco market resembled less to an arena of effective state intervention and smooth functioning under legislations. Rather, conflicts over the forms of state intervention and the institutional failures determined the relations among the market actors as well as the tobacco policies. Fourth, this dissertation reveals the compulsory levy imposed on tobacco producers for eleven years from 194 7 to 1957 with a promise to establish a regulatory institution. Given the promise never kept and a substantial fund raised, the direct monetary cuts from producers were a hidden taxation practice in the Turkish agriculture. The fate ofthe producer fund brings the fifth conclusion of this study. Support purchases in the Turkish tobacco market were primarily financed with producers' own money. Sixth, the Turkish political authorities, including seemingly more agriculture-friendly center-right parties, were never dare enough to shoulder the structural transformation the tobacco market needed. The crisis at the end of the 1970s and the following liberalization in the early 1980s owed so much to such a lack of reform initiative for the existing market order.
Keywords: Tobacco -- Turkey.; Tobacco -- Turkey -- History.; Tobacco -- Social aspects -- Turkey.